NEGOSIASI TRADISI DI RUANG MODERN: ANALISIS SOSIO-ANTROPOLOGIS PRAKTIK TAHLILAN PADA MAHASISWA DI JAWA BARAT - Ghina Nur Rohmah; Mochammad Saefaturrohman N.; Annisa Dea S.; Aulia Nurhasanah S.; Dini Novitasari (Yayasan Literasi Sains Indonesia, 2026)
The tradition of tahlilan is deeply rooted in Indonesian Muslim communities, especially among Nahdlatul Ulama, as a religious practice to pray for the deceased. However, in the context of modern society, the meaning and implementation of tahlilan have undergone dynamics, especially among students. Therefore, this study aims to explore the community's perspective on the tradition of tahlilan and the values contained therein. This study uses a qualitative descriptive method through in-depth interviews with 11 students from the Indonesia University of Education (UPI), 1 student from the Bandung Institute of Technology (ITB), 1 student from the Raden Mas Said Surakarta State Islamic University, as well as the Secretary of the Indonesian Ulema Council (MUI) at the West Java Provincial level and the Deputy Katib Suriah Nahdlatul Ulama (NU) at the West Java Provincial level. The results of the study show that students generally recognize and acknowledge tahlilan as a religious tradition that has spiritual, social, and cultural values. However, student participation in tahlilan tends to be low and situational due to academic commitments. These findings indicate a discrepancy between the recognition of the value of tahlilan and its actual practice, and confirm that tahlilan is a religious practice that continues to undergo adjustments amid social change.